DAMPAK BERBAGI HIBURAN UNTUK NILAI-NILAI KONSUMEN PADA VIDEO KOMERSIAL DAN EKUITAS MEREK PADA MIXUE JAKARTA - Christian Niscal Ziliwu; Margaretha Pink Berlianto (Faculty of Economics and Business Universitas Pelita Harapan, 2023)
Internet users in recent years have experienced rapid growth due to rapid developments in technological devices, mobile applications, and internet connections. For Indonesia itself, the use of social media has also become a trend that is no less widely used. Mixue's ice cream and sweet drink outlets are